Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1093/humupd/2.4.345
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of major clinical complications in a Dutch transport IVF programme

Abstract: Four different major clinical complications were identified in a retrospective analysis of 2495 in-vitro fertilization (IVF) cycles resulting in oocyte retrieval. The severe form of ovarian hyperstimulation syndrome (OHSS) occurred in 18 patients, giving a prevalence for this complication of 0.7%. Seven (39%) of these 18 patients had previously been diagnosed as having polycystic ovaries. Eleven patients were admitted with moderate OHSS. Adnexal torsion was diagnosed in two patients. Ovariectomy was considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 76 publications
(97 reference statements)
4
39
1
2
Order By: Relevance
“…However, the incidence is generally low and varies between 0.03% and 1.3% (7,(21)(22)(23)(24)(25)(26)(27). Transvaginal inoculation of bacteria into the peritoneal cavity or ovary by the collecting needle is the most apparent source of these infections (23,28,29).…”
mentioning
confidence: 99%
“…However, the incidence is generally low and varies between 0.03% and 1.3% (7,(21)(22)(23)(24)(25)(26)(27). Transvaginal inoculation of bacteria into the peritoneal cavity or ovary by the collecting needle is the most apparent source of these infections (23,28,29).…”
mentioning
confidence: 99%
“…Akman et al and Roest et al reported perforated appendicitis in two patients after OPU, and the needle hole was observed in these cases [25,26]. Contrary to what is believed, intestinal injury is less common, and is more likely to develop in patients with advanced endometriosis, previous surgery, or pelvic adhesions related to previous infections [27].…”
Section: Discussionmentioning
confidence: 97%
“…In their series of 2.495 patients, Roest et al detected pelvic infection in six (0.24%) patients. These six patients were treated with appropriate antibiotics [26]. Askenazi et al [31] found pelvic infection in 28 of 47.771 patients (0.58%).…”
Section: Discussionmentioning
confidence: 99%
“…6 Proflaktik antibiyotik kullanımını öneren kanıta dayalı bir rehber bulunmasa da doksisiklin, metronidazol ya da birinci kuşak sefalosporinleri OPU öncesi profilaktik dozda kullanarak ya da OPU günü ve sonrasında kullanılmak üzere 5 gün-lük antibiyoterapi rejimi düzenleyerek enfeksiyonu azalttıklarını bildiren farklı çalışmalar bulunmaktadır. [7][8][9] Bu konudaki tek ortak görüş ise daha ön-ceden PIH geçirmiş ya da endometrioması olan hastalar gibi yüksek riskli hastalarda antibiyotik kullanılması gerekliliğidir. 10 Bu hastalarda pelvik abse ile sonuçlanabilen enfeksiyonlar bildirilmektedir.…”
Section: Enfeksi̇yonunclassified